Case Report : Bronchiolitis - Inggrit Anggraini; Supriadi Supriadi; Muhammad Yoga Rizki Danil; Destri Linjani (Lembaga Pengembangan Kinerja Dosen, 2025)
Bronchiolitis is an acute inflammatory injury to the bronchioles usually caused by a viral infection (most commonly respiratory syncytial virus). This condition can occur in people of any age, but severe symptoms are usually only seen in young babies.